Calculating tidal prediction in the Gulf of Tonkin - Do Ngoc Quynh; Nguyen Thi Viet Lien (Vietnam Journal of Mechanics, 1995)
In the paper the using numerical hydro dynamical model for the tidal prediction in the Gulf of Tonkin is presented. The results of prediction are compared with the Tidal Table at some coastal station. The comparison proves that the prediction model suits practice.